2013
DOI: 10.9790/3021-03425459
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Binary Blended Cement Composites Containing Plantain Leaf Ash

Abstract: Abstract:The strength characteristics of binary blended cement composites made with Ordinary Portland Cement (OPC) and Plantain Leaf Ash (PLA) were investigated in this work. 105 concrete cubes and 105 sandcrete cubes of 150mm x 150mm x 150mm were produced at percentage OPC replacement with PLA of 5%, 10%, 15%, 20%, and 25% and crushed to obtain their compressive strengths at 3, 7, 14, 21, 28, 50, and 90 days of curing. The 3-21 day compressive strength values of OPC-PLA binary blended cement concrete were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The studies of Elinwa and Abdulkadir [9] confirmed SDA as posolinic material and reducing porosity as well as being effective in reducing corrosion of reinforcement. Recent studies by Ettu et al [10] have confirmed the suitability of Nigerian SDA as pozzolanic material for producing concrete, sandcrete or soilcrete. Otoko and Honest [11] carried research on stabilization of Nigerian deltaic laterites with SDA.…”
mentioning
confidence: 98%
“…The studies of Elinwa and Abdulkadir [9] confirmed SDA as posolinic material and reducing porosity as well as being effective in reducing corrosion of reinforcement. Recent studies by Ettu et al [10] have confirmed the suitability of Nigerian SDA as pozzolanic material for producing concrete, sandcrete or soilcrete. Otoko and Honest [11] carried research on stabilization of Nigerian deltaic laterites with SDA.…”
mentioning
confidence: 98%
“…J. PAW PAW LEAF ASH L. O. Ettu et al, carried out a detailed study on the strength characteristics of paw paw leaf ash (PPLA) blended cement composites. Even though the strength of PPLA blended concrete was lower than that of control mix during initial days of curing, at 90 days of curing, for 5-10% replacement percentage, the strength of PPLA blended concrete was better than that of control mix concrete [70]. L. O. Ettu et al, worked on the strength aspect of ternary blended cement concrete containing corn cob ash and paw paw leaf ash.…”
Section: H Olive Waste Ashmentioning
confidence: 99%
“…Also, depletion of lime stone deposits at faster rate and demand of other raw materials are disadvantages in cement production. [7]. Production of Portland cement rate is lesser than that of demand rate and hence the cement price is increasing continuously.…”
Section: Alternate Binding Materialsmentioning
confidence: 99%